Multiple spinal neurofibromas - Kodeeswaran Marappan; Prabhu Marudamuthu; Sherina Paul Raj (Apollo Medicine)
A 55-year-old male, with a 2-month history of urinary incontinence, a suspected case of pyelonephritis was initially treated by a nephrologist, but with no relief in spite of medication. On further evaluation, he was found to have a history of back pain, progressive bilateral weakness of lower extremities, and difficulty walking. He was thus referred to us for further management. Magnetic resonance imaging (MRI) of the spine was done, which revealed the presence of multiple bilateral dumbbell-shaped lesions at multiple spinal levels, associated with widening of the neural foramina of the cervical, dorsal, and lumbar regions. Surgical excision of all lesions was done in a single sitting. The patient had postoperative weakness and urinary incontinence, which slowly recovered and weakness gradually improved by physiotherapy. On follow-up, the patient was able to walk without any weakness. Surgical excision is the treatment of choice for spinal neurofibromatosis. Diagnosis of the condition may be difficult due to the lack of symptoms in majority of the cases or presentation with rare symptoms. However, it is recommended that a routine MRI of the spine be performed in patients with a history of urinary incontinence associated with weakness of limbs.